Vaporization characteristics of ethanol droplets: Influence of the environment humidity - Saharin, Sanisah; Lefort, Benoite; Morin, Celine; Chauveau, Christian; Le Moyne, Luis; Kafafy, Raed (2011)
The study of the gasification of a droplet via vaporization, which involves heat, mass and momentum transfer processes in gas and liquid phases, and their coupling at the droplet interface, is necessary for better understanding and modeling of complex spray and mixture formation issues. A detailed description of the vaporization of an isolated droplet has been realized in this experimental study aimed at investigating the impact of the water vapor contained in the surrounding gas on the evaporation of an ethanol droplet. The experimental set-up consists of a heated chamber with a cross quartz fibers configuration as droplet support. An ethanol droplet is located at the intersection of the cross with a controlled initial diameter (300 - 550µm). Ambient temperature is varied from 350 to 850 K. The real impact of the water concentration on the vaporization rate of an ethanol droplet in a large range of temperature is examined, showing that the vaporization of an ethanol droplet is accompanied by the simultaneous condensation of water vapour on the droplet surface and thus the temporal evolution of the droplet squared diameter exhibits an unsteady behaviour. The histories of the instantaneous vaporisation rates calculated from the d²(t) curves confirms this non-stationary aspect of the phenomenon.